DUMPSTER DIVING THREAT IN PERSONAL DATA LEAKAGE CASE IN INDONESIA - Noval, Sayid Muhammad Rifki; Soecipto, Soecipto; Jamaludin, Ahmad; Listiawati, Erna (Research Collaboration Community (Rescollacom), 2023)
It is a big job for law enforcement to be able to deal with fraud crimes and data leaks that are increasing at this time. Social engineering attacks are considered to be one of the modes used by perpetrators in carrying out their actions. If the current prevention efforts always link social engineering with phishing, an activity that is closely related to technological sophistication, it is necessary to know another form of social engineering that deserves attention, namely dumpster diving. A term that describes the activity of “scavenging” a target's trash in search of valuable information. Dumpster diving is often underestimated because some people think that if the waste that has been disposed of will not be used by others, it will even have a threatening impact. The habit of throwing away records and documents without being destroyed makes it a target for perpetrators to collect information which will then be used in attacking their targets. Several countries have considered regulating the designation of waste that has the potential to be misused, including regarding the security of personal data. Therefore, this article aims to provide an alternative policy for the Indonesian government, in order to consider the issuance of regulations that protect victims who are affected by losses due to the use of waste by perpetrators.